2006
DOI: 10.1093/schbul/sbl016
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Insight Paradox: Internalized Stigma Moderates the Association Between Insight and Social Functioning, Hope, and Self-esteem Among People with Schizophrenia Spectrum Disorders

Abstract: Research has paradoxically linked awareness of illness to both better function outcomes and lesser hope and self-esteem. One possible explanation for these findings is that acceptance of having schizophrenia may impact outcomes differently depending on the meanings the person attaches to this acceptance, particularly whether he or she accepts stigmatizing beliefs about mental illness. To explore this possibility we performed a cluster analysis of 75 persons with schizophrenia spectrum disorders based on single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
397
8
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(454 citation statements)
references
References 48 publications
36
397
8
13
Order By: Relevance
“…Replicating earlier research 75 , several groups have found that the link between insight and depression was mediated by self-stigma [82][83][84] . Others have suggested that, beyond stigma, a generally negative appraisal of one's future 85 and tendency to ruminate 79 influence the effects of insight on mood.…”
Section: Good Clinical Insight Is Associated With Depression and Poormentioning
confidence: 57%
See 1 more Smart Citation
“…Replicating earlier research 75 , several groups have found that the link between insight and depression was mediated by self-stigma [82][83][84] . Others have suggested that, beyond stigma, a generally negative appraisal of one's future 85 and tendency to ruminate 79 influence the effects of insight on mood.…”
Section: Good Clinical Insight Is Associated With Depression and Poormentioning
confidence: 57%
“…In what may be referred to as the "insight paradox", earlier research suggested that good clinical insight may produce distress and compromise well-being 75 . Consistent with this, studies of diverse samples continue to find good insight to be correlated with depression and related constructs such as hopelessness 29,52,74,[76][77][78][79] .…”
Section: Good Clinical Insight Is Associated With Depression and Poormentioning
confidence: 99%
“…With replication this might suggest that a useful element of counseling for persons with schizophrenia might involve both assisting them to address stigma when they encounter it in routine life but also to openly explore concerns about how stigma affects the counseling relationship (c.f. Lysaker et al, 2007b). As with all unexpected findings though, further research is necessary before any weight is afforded these speculations.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with this model, there is considerable evidence from cross-sectional studies to suggest that possessing good insight in psychosis is associated with measures of distress, such as depression (see Lincoln, Lüllmann & Rief, 2007), hopelessness (Carroll et al, 2004, Eneman & Sabbe, 2006Schwartz, Apter & Zalsman, 2006;Lysaker, Roe & Yanos, 2007), anxiety (Lysaker & Salyers, 2007) and suicidability (Schwartz et al, 2004, Crumlish et al, 2005Pompili et al, 2007). Although some longitudinal studies suggest that increases in insight are associated with worsening measures of distress and depression (Carroll et al, 1999;Iqbal et al, 2000;Schartz, 2001;Drake et al, 2004;Lincoln, Lüllmann & Rief, 2007), the existing evidence is still weak so that the direction of causality needs to be explored in future well designed longitudinal studies.…”
Section: Models Of Poor Insight In Psychosismentioning
confidence: 94%